Acute myopathy following intra-muscular injection of compound betamethasone: A case report. Issue 34 (August 2017) - Sun, Li-Yuan; Chu, Xiao-Ling
Abstract: Rationale: We report a case of acute steroid myopathy in a patient with eczema receiving one dose of intra-muscular injection of Compound betamethasone. Patient concerns: Acute steroid myopathy (ASM) is usually caused by exogenous corticosteroids, and typically, occurs with therapy using intravenous corticosteroids at high doses. Diagnoses: The patient was considered as a diagnosis of acute steroid myopathy. Interventions: The patient was treated with non-steroid anti-inflammatory drug and other symptomatic therapy. Outcomes: ASM was gradually improved after 2 weeks symptomatic treatment and completely recovered after one-month treatment. Lessons: The diagnosis of steroid myopathy is a clinical diagnosis based on characteristic symptoms. Higher dose of steroids, especially fluorinated steroids, for longer periods of time increases the risk of steroid-induced myopathy.